Implementation in education quality assurance and quality improvement of primary school education - Eliawati, Titim; Dewi, Rosmala; Purba, Saut; Purba, Sukarman (Institute of Computer Science (IOCS), 2024)
The purpose of this study was to obtain a complete description of the implementation of quality assurance at the primary school level. Implementation of education quality assurance and improving the quality of primary school education involves various aspects, such as internal quality assurance systems, teacher competency tests, management of educators and education personnel, and self-evaluation models. To realize further research on the development of quality assurance models, especially at the primary education level, preliminary research is needed to map the actual conditions in primary schools. The research approach used in this study is a descriptive qualitative approach. Data collection techniques used in this research are observation, interviews, and documentation. Then the data analysis technique used is interactive model data analysis. the implementation of the education quality assurance system in improving school quality will be carried out well if all education stakeholders are involved and support quality planning. There needs to be adequate budget support in preparing quality. There are obstacles in the implementation of education quality assurance, to improve school quality. There are ways to overcome some of the obstacles to the implementation of the education quality assurance system to improve school quality, namely being able to improve the results of fulfilling quality, increasing targets that have not been achieved, improving the findings, increasing possible aspects, and setting more quality targets so that each aspect can be followed up and improved to improve school quality.